Preparation method of anti-fouling wall paint

By using silicone modified acrylic emulsion in wall paint and synergistic nanotitanium dioxide, combined with specially treated diatomaceous earth and nano-scale hollow glass microbeads, the problem of wall paint restricting water vapor exchange while blocking stain invasion, achieving an improvement in soil resistance, breathability and service life.

CN119708942APending Publication Date: 2025-03-28GUANGZHOU YIWEI BUILDING MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510065062.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

While preventing stains from invading, existing wall paint restricts the exchange of water vapor between the wall and the outside world, resulting in the accumulation of water vapor inside the wall, which may cause problems such as bubbles, mold, and fall off, especially in environments with high humidity.

Method used

Silicone modified acrylic emulsion and modified nanotitanium dioxide are used to work synergistically, combined with specially treated diatomaceous earth and nano-scale hollow glass microbeads, and through fine preparation technology and raw material ratio, wall paint with comprehensive properties such as stain resistance, self-cleaning, and breathable are formed.

Benefits of technology

It has achieved improved stain resistance and breathability of wall paint, avoided bubbles, mold and fall off caused by accumulation of water vapor, and extended the service life and protective effect of wall paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708942A_ABST
    Figure CN119708942A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of wall paint, in particular to a preparation method of anti-fouling wall paint. According to the technical scheme, the preparation method comprises the steps of preparation of organic silicon modified acrylic emulsion and preparation of modified nano titanium dioxide. And then weighing the following raw materials in parts by weight: 30-40 parts of organic silicon modified acrylic emulsion, 5-8 parts of modified titanium dioxide, 10-15 parts of diatomite, 3-5 parts of nanoscale hollow glass beads, 2-3 parts of a coalescing agent, 0.5-1 part of a polymeric dispersant and 0.3-0.5 part of an organic silicon defoaming agent. According to the invention, the organic silicon modified acrylic emulsion, modified nano titanium dioxide, specially-treated diatomite, nano-scale hollow glass beads and the like are used as raw materials, so that the performances such as water resistance, pollution resistance, self-cleaning and air permeability are improved; in the preparation process, the emulsion is prepared finely, the raw materials are mixed uniformly, the product quality is guaranteed, the construction efficiency is improved, and the using effect of the wall paint is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wall paint preparation, and in particular to a method for preparing anti-fouling wall paint. Background Art

[0002] In order to achieve good anti-fouling performance, this type of wall paint often forms a denser paint film on the surface, which can effectively block the invasion of stains, but also limits the water vapor exchange between the wall and the outside world. If there is a certain humidity in the wall base itself, the moisture cannot be dissipated through the paint film, and it is easy to accumulate inside the wall. Over time, it may cause bubbling, mildew, and shedding problems on the wall, especially in environments with high humidity, such as the plum rain season in the south or in areas such as bathrooms and kitchens. These problems may be more obvious, not only affecting the beauty of the wall, but also reducing the service life and protective effect of the wall paint. Therefore, the present application proposes a method for preparing an anti-fouling wall paint. Summary of the invention

[0003] The purpose of the invention is to provide a method for preparing anti-fouling wall paint in view of the problems of bubbling, mildew and shedding of wall paint in the background technology.

[0004] The technical solution of the present invention is a method for preparing an anti-fouling wall paint, comprising the following steps: Step S1, preparation of silicone-modified acrylic emulsion, specifically comprising: 75-85 parts by weight of deionized water are added to a four-necked flask equipped with a stirring device, a reflux condenser, a thermometer and a dropping funnel, stirring is started, the speed is set to 100-200 rpm, and 0.08-0.12 parts of sodium bicarbonate buffer are added to completely dissolve the mixture; Slowly raise the temperature to 80-90°C and maintain a constant temperature, add 10-20 parts of vinyltrimethoxysilane into the four-necked flask within 15-25 minutes to make it preliminarily evenly dispersed in the reaction system; Methyl acrylate and methyl methacrylate are mixed in a mass ratio of 1:1 as acrylic acid monomers, 55-65 parts of the mixed acrylic acid monomers are added dropwise through a dropping funnel within 1-2 hours, and 0.3-0.5 parts of an initiator solution prepared by ammonium persulfate are added dropwise at a uniform speed; After the dropwise addition is completed, the reaction is continued to be stirred for 3-5 hours. During the reaction, the volatile substances generated by the reaction are promptly removed through a reflux condenser to maintain the stability of the reaction system. After the reaction is completed, the mixture is cooled to room temperature, and unreacted monomers are removed by vacuum distillation at a pressure of -0.08 MPa. The emulsion is filtered through a 100-200 mesh filter to remove possible insoluble particles, thereby obtaining an organosilicon-modified acrylic emulsion; Step S2, preparation of modified nano titanium dioxide, using nano titanium dioxide with a particle size between 20-50 nanometers for surface modification, using silane coupling agent KH570, adding 1%-3% of the mass of nano titanium dioxide, reacting for 1-2 hours under high-speed stirring to obtain modified nano titanium dioxide; Step S3, weighing the following raw materials in parts by weight: 30-40 parts of organosilicon-modified acrylic emulsion, 5-8 parts of modified titanium dioxide, 10-15 parts of diatomaceous earth, 3-5 parts of nano-scale hollow glass microspheres, 2-3 parts of film-forming aid, 0.5-1 part of polymer dispersant, 0.3-0.5 parts of organosilicon defoamer, 0.2-0.5 parts of cellulose thickener, and 10-20 parts of pigment; Step S4, pre-dispersion stage: add deionized water to a high-speed stirring device, start stirring at a speed of 300-500 rpm, add a dispersant, stir for 10-15 minutes to completely dissolve it, then add modified nano titanium dioxide, diatomaceous earth, hydrophilic treated nano hollow glass microspheres and pigment in sequence, and continue stirring for 30-60 minutes; Step S5, emulsion mixing stage: reducing the stirring speed to 100-200 rpm, adding the organosilicon-modified acrylic emulsion, and continuing stirring for 15-30 minutes after the emulsion is added; Step S6, additive adding stage: add film-forming additive, defoamer and thickener in sequence, stir for 5-10 minutes after adding each additive, then grind and filter to obtain wall paint.

[0005] Optionally, the diatomaceous earth is treated before use, and the specific steps are: first calcining the diatomaceous earth at a high temperature of 800-1000°C for 2-3 hours, then acid-treating it with a 5%-10% hydrochloric acid solution, soaking it for 3-5 hours, then repeatedly rinsing it with deionized water until it is neutral, and drying it for use.

[0006] Optionally, the nanoscale hollow glass microspheres are hydrophilically treated before use, specifically using a composite system of surfactants Span-80 and Tween-80, with a mass ratio of 1:1 and an addition amount of 0.5%-1% of the mass of the hollow glass microspheres, and ultrasonically dispersed for 30-60 minutes for use.

[0007] Optionally, the film-forming aid is propylene glycol ester-12 or propylene glycol phenyl ether.

[0008] Optionally, the defoaming agent is BYK022 or BYK028.

[0009] Optionally, the thickener is hydroxyethyl cellulose or a hydrophobically modified alkali-swellable thickener.

[0010] Optionally, in step S3, weigh the following raw materials in parts by weight: 32-38 parts of silicone-modified acrylic emulsion, 5-7 parts of modified titanium dioxide, 11-14 parts of diatomaceous earth, 4-5 parts of nanoscale hollow glass microspheres, 2-3 parts of film-forming aid, 0.6-0.8 parts of polymer dispersant, 0.4-0.5 parts of silicone defoaming agent, 0.2-0.4 parts of cellulose thickener, and 12-18 parts of pigment.

[0011] Optionally, in step S3, the following raw materials are weighed in parts by weight: 35 parts of organosilicon-modified acrylic emulsion, 6.5 parts of modified titanium dioxide, 12.5 parts of diatomaceous earth, 4 parts of nano-scale hollow glass microspheres, 2.5 parts of film-forming aid, 0.75 parts of polymer dispersant, 0.4 parts of organosilicon defoaming agent, 0.35 parts of cellulose thickener, and 15 parts of pigment.

[0012] Optionally, the grinding specifically includes: transferring the mixed material to a sand mill, using zirconium oxide beads as the grinding medium, controlling the particle size between 0.1 and 1 mm, and filling 50% to 70% of the volume of the grinding equipment. The grinding time is 2 to 4 hours, the grinding temperature is controlled at 20 to 40°C by circulating cooling water, and the material fineness reaches 15 to 20 microns after multiple cycles of grinding, and the material fineness is tested by a laser particle size analyzer to ensure that the requirements are met.

[0013] Optionally, the filtering specifically includes: filtering the ground wall paint through a 100-200 mesh filter to obtain the wall paint.

[0014] Compared with the prior art, the present invention has at least one of the following beneficial technical effects: In the present invention, the organosilicon-modified acrylic emulsion is used as the main film-forming substance, and it cooperates with the modified nano titanium dioxide to enhance the comprehensive performance of the paint film. The photocatalytic activity of the nano titanium dioxide decomposes organic pollutants, and the paint film formed by the emulsion provides a stable adhesion basis for it. The combination of the two makes the wall paint not only anti-fouling, but also can continuously purify the air. At the same time, the flexibility and adhesion of the emulsion cooperate with diatomaceous earth and nano-scale hollow glass microspheres to maintain the integrity of the paint film while ensuring air permeability, and avoid reducing the strength of the paint film due to the addition of air permeable components.

[0015] Film-forming aids are further used to help the emulsion form a continuous and dense paint film at a suitable temperature, dispersants ensure that the emulsion is evenly mixed with other solid particles, defoamers eliminate bubbles generated during the production process, and thickeners adjust the viscosity of the system. They work together to ensure that the wall paint maintains good performance during storage, construction and use.

[0016] In addition, the adsorption of diatomite is combined with the photocatalytic activity of nano-titanium dioxide. Organic pollutants adsorbed by diatomite can be more efficiently decomposed by nano-titanium dioxide, thereby improving the purification capacity of wall paint. In addition, the presence of nano-titanium dioxide may also inhibit the growth of microorganisms on the surface of diatomite to a certain extent, maintaining the long-term stability of diatomite's adsorption performance.

[0017] Furthermore, diatomite and nano-scale hollow glass microspheres have a significant synergistic effect in improving air permeability. The microporous structure of diatomite and the void channels of hollow glass microspheres complement each other to form a more complete air permeability network, greatly improving the air permeability of wall paint. At the same time, the two also work together to regulate the humidity of the wall. After diatomite absorbs moisture, the channels formed by hollow glass microspheres help the diffusion and evaporation of moisture, so that the humidity of the wall can be better balanced, effectively preventing various adverse phenomena caused by humidity problems on the wall.

[0018] In summary, the present invention uses silicone-modified acrylic emulsion, modified nano titanium dioxide, specially treated diatomaceous earth and nano-scale hollow glass microspheres to improve the water resistance, anti-fouling, self-cleaning, breathability and other performances. In terms of preparation process, the emulsion is prepared finely and the raw materials are mixed evenly, which ensures product quality, improves construction efficiency, and makes the wall paint have a better use effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a flow chart of a method for preparing an antifouling wall paint. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0021] Embodiment 1:

[0022] like Figure 1 As shown, a method for preparing an anti-fouling wall paint proposed by the present invention, the steps are described in detail below.

[0023] Preparation of silicone-modified acrylic emulsion: 75 parts of deionized water are added to a four-necked flask with a stirring device, a reflux condenser, a thermometer and a dropping funnel by weight, stirring is started, the speed is set to 100 rpm, 0.08 parts of sodium bicarbonate buffer is added to completely dissolve it; the temperature is slowly raised to 80°C and kept constant, 10 parts of vinyl trimethoxy silane are added to the four-necked flask within 15 minutes to make it preliminarily evenly dispersed in the reaction system; methyl acrylate and methyl methacrylate are selected as acrylic monomers and mixed in a mass ratio of 1:1, and the mixture is passed through a dropping funnel. Add 55 parts of the mixed acrylic acid monomer dropwise within 1 hour, and simultaneously add 0.3 parts of an initiator solution prepared by ammonium persulfate dropwise at a uniform speed; continue stirring and reacting for 3 hours after the addition is completed, and in the reaction process, remove the volatile substances produced by the reaction in time through a reflux condenser to maintain the stability of the reaction system; after the reaction is completed, cool to room temperature, remove the unreacted monomers by a reduced pressure distillation method at a pressure of -0.08 MPa, and filter the emulsion with a 100-mesh filter to remove possible insoluble particles to obtain an organosilicon-modified acrylic acid emulsion; Preparation of modified nano titanium dioxide: using nano titanium dioxide with a particle size between 20 and 50 nanometers for surface modification, adding silane coupling agent KH570 at 1% of the mass of nano titanium dioxide, reacting for 1 hour under high-speed stirring to obtain modified nano titanium dioxide; First, calcine the diatomite at a high temperature of 800°C for 2 hours, then treat it with a 5% hydrochloric acid solution for 3 hours, then rinse it repeatedly with deionized water until it is neutral, and dry it for later use; The nano-scale hollow glass microspheres were hydrophilized before use, specifically using a composite system of surfactants Span-80 and Tween-80, with a mass ratio of 1:1 and an addition amount of 0.5% of the mass of the hollow glass microspheres, and then dispersed by ultrasound for 30 minutes for use; Weigh the following raw materials in parts by weight: 30 parts of organosilicon-modified acrylic emulsion, 5 parts of modified titanium dioxide, 10 parts of diatomaceous earth, 3 parts of nano-scale hollow glass microspheres, 2 parts of film-forming aid, 0.5 parts of polymer dispersant, 0.3 parts of organosilicon defoamer, 0.2 parts of cellulose thickener, and 10 parts of pigment. The film-forming aid is alcohol ester-12, the defoamer is BYK022, and the thickener is hydroxyethyl cellulose; Pre-dispersion stage: add deionized water to the high-speed stirring equipment, start stirring at a speed of 300 rpm, add dispersant, stir for 10 minutes to completely dissolve it, then add modified nano titanium dioxide, diatomaceous earth, hydrophilic treated nano hollow glass microspheres and pigment in sequence, and continue stirring for 30 minutes; Emulsion mixing stage: reduce the stirring speed to 100 rpm, add the silicone-modified acrylic emulsion, and continue stirring for 15 minutes after the emulsion is added; Additive addition stage: add film-forming additive, defoamer and thickener in sequence, stir for 5 minutes after adding each additive, and then transfer the mixed material to the sand mill. Use zirconium oxide beads as grinding media, and control the particle size between 0.1-1.0 mm. The filling amount is 50% of the volume of the grinding equipment. The grinding time is 2 hours, and the grinding temperature is controlled at 20°C by circulating cooling water. After multiple cycles of grinding, the material fineness reaches 15-20 microns. The material fineness is tested by a laser particle size analyzer to ensure that it meets the requirements. The ground wall paint is filtered through a 100-mesh filter to obtain the wall paint.

[0024] Embodiment 2:

[0025] like Figure 1 As shown, a method for preparing an anti-fouling wall paint proposed by the present invention, the steps are described in detail below.

[0026] Preparation of silicone-modified acrylic emulsion: 78 parts of deionized water are added to a four-necked flask with a stirring device, a reflux condenser, a thermometer and a dropping funnel, stirring is started, the speed is set to 120 rpm, 0.09 parts of sodium bicarbonate buffer are added to completely dissolve it; the temperature is slowly raised to 83°C and kept constant, 13 parts of vinyl trimethoxy silane are added to the four-necked flask within 18 minutes to make it preliminarily uniformly dispersed in the reaction system; methyl acrylate and methyl methacrylate are selected as acrylic monomers in a mass ratio of 1:1, and a dropping funnel is used to precipitate 100 g of methyl methacrylate and 100 g of methyl methacrylate. . Add 58 parts of the mixed acrylic acid monomer dropwise within 2 hours, and simultaneously add 0.4 parts of the initiator solution prepared by ammonium persulfate dropwise at a uniform speed; continue to stir and react for 3.5 hours after the addition is completed. During the reaction, the volatile substances produced by the reaction are promptly removed through a reflux condenser to maintain the stability of the reaction system. After the reaction is completed, cool to room temperature, and remove the unreacted monomers by vacuum distillation at a pressure of -0.08MPa. Filter the emulsion with a 120-mesh filter to remove possible insoluble particles to obtain an organosilicon-modified acrylic emulsion; Preparation of modified nano titanium dioxide: using nano titanium dioxide with a particle size between 20 and 50 nanometers for surface modification, using silane coupling agent KH570, adding 1.5% of the mass of nano titanium dioxide, reacting for 1.2 hours under high-speed stirring to obtain modified nano titanium dioxide; First, calcine the diatomite at a high temperature of 850°C for 2.2 hours, then treat it with a 6% hydrochloric acid solution for 3.5 hours, then rinse it repeatedly with deionized water until it is neutral, and dry it for later use; The nano-scale hollow glass microspheres were hydrophilized before use, specifically using a composite system of surfactants Span-80 and Tween-80, with a mass ratio of 1:1 and an addition amount of 0.6% of the mass of the hollow glass microspheres, and then dispersed by ultrasound for 40 minutes for use; Weigh the following raw materials in parts by weight: 32 parts of organosilicon-modified acrylic emulsion, 6 parts of modified titanium dioxide, 12 parts of diatomaceous earth, 3.5 parts of nano-scale hollow glass microspheres, 2.2 parts of film-forming aid, 0.6 parts of polymer dispersant, 0.35 parts of organosilicon defoamer, 0.25 parts of cellulose thickener, and 12 parts of pigment, wherein the film-forming aid is propylene glycol phenyl ether, the defoamer is BYK028, and the thickener is a hydrophobically modified alkali swelling thickener; Pre-dispersion stage: add deionized water to the high-speed stirring equipment, start stirring at a speed of 350 rpm, add dispersant, stir for 12 minutes to completely dissolve it, then add modified nano titanium dioxide, diatomaceous earth, hydrophilic treated nano hollow glass microspheres and pigment in sequence, and continue stirring for 35 minutes; Emulsion mixing stage: reduce the stirring speed to 120 rpm, add the silicone-modified acrylic emulsion, and continue stirring for 20 minutes after the emulsion is added; Additives adding stage: add film-forming additives, defoamers, thickeners in turn, stir for 6 minutes after adding each additive, and then transfer the mixed materials to the sand mill. The grinding medium is zirconium oxide beads, the particle size is controlled between 0.1-1.0 mm, and the filling amount is 55% of the volume of the grinding equipment. The grinding time is 2.5 hours, and the grinding temperature is controlled at 25°C by circulating cooling water. After multiple cycles of grinding, the material fineness reaches 15-20 microns. The material fineness is tested by a laser particle size analyzer to ensure that it meets the requirements. The ground wall paint is filtered through a 120-mesh filter to obtain the wall paint.

[0027] Embodiment 3:

[0028] like Figure 1 As shown, a method for preparing an anti-fouling wall paint proposed by the present invention, the steps are described in detail below.

[0029] Preparation of silicone-modified acrylic emulsion: 80 parts by weight of deionized water are added to a four-necked flask equipped with a stirring device, a reflux condenser, a thermometer and a dropping funnel, stirring is started, the speed is set to 150 rpm, 0.1 parts of sodium bicarbonate buffer are added to completely dissolve it; the temperature is slowly raised to 85°C and kept constant, 15 parts of vinyl trimethoxy silane are added to the four-necked flask within 20 minutes to make it preliminarily uniformly dispersed in the reaction system; methyl acrylate and methyl methacrylate are selected as acrylic monomers in a mass ratio of 1:1, and a dropping funnel is used to precipitate 100% methacrylate. .5 hours, dropwise add 60 parts of the mixed acrylic acid monomer, and simultaneously dropwise add 0.4 parts of the initiator solution prepared by ammonium persulfate at a uniform speed; after the dropwise addition is completed, continue to stir and react for 4 hours, during the reaction, remove the volatile substances produced by the reaction in time through the reflux condenser to maintain the stability of the reaction system, after the reaction is completed, cool to room temperature, use the reduced pressure distillation method at a pressure of -0.08MPa to remove the unreacted monomer, filter the emulsion with a 150-mesh filter to remove possible insoluble particles, and obtain an organosilicon-modified acrylic emulsion; Preparation of modified nano titanium dioxide: using nano titanium dioxide with a particle size between 20 and 50 nanometers for surface modification, using silane coupling agent KH570, adding 2% of the mass of nano titanium dioxide, reacting for 1.5 hours under high-speed stirring to obtain modified nano titanium dioxide; First, calcine the diatomite at a high temperature of 900°C for 2.5 hours, then treat it with a 7.5% hydrochloric acid solution for 4 hours, then rinse it repeatedly with deionized water until it is neutral, and dry it for later use; The nano-scale hollow glass microspheres were hydrophilized before use, specifically using a composite system of surfactants Span-80 and Tween-80, with a mass ratio of 1:1 and an addition amount of 0.75% of the mass of the hollow glass microspheres, and then dispersed by ultrasound for 45 minutes for use; Weigh the following raw materials in parts by weight: 35 parts of organosilicon-modified acrylic emulsion, 6.5 parts of modified titanium dioxide, 12.5 parts of diatomaceous earth, 4 parts of nano-scale hollow glass microspheres, 2.5 parts of film-forming aid, 0.75 parts of polymer dispersant, 0.4 parts of organosilicon defoamer, 0.35 parts of cellulose thickener, 15 parts of pigment, the film-forming aid is alcohol ester-12, the defoamer is BYK028, and the thickener is hydroxyethyl cellulose; Pre-dispersion stage: add deionized water to the high-speed stirring equipment, start stirring at a speed of 400 rpm, add dispersant, stir for 12.5 minutes to completely dissolve it, then add modified nano titanium dioxide, diatomaceous earth, hydrophilic treated nano hollow glass microspheres and pigment in sequence, and continue stirring for 45 minutes; Emulsion mixing stage: reduce the stirring speed to 150 rpm, add the silicone-modified acrylic emulsion, and continue stirring for 22.5 minutes after the emulsion is added; Additive addition stage: add film-forming additive, defoamer, thickener in turn, stir for 7.5 minutes after adding each additive, then transfer the mixed material to the sand mill, use zirconium oxide beads as grinding media, the particle size is controlled between 0.1-1 mm, and the filling amount is 60% of the volume of the grinding equipment. The grinding time is 3 hours, and the grinding temperature is controlled at 30°C by circulating cooling water. After multiple cycles of grinding, the material fineness reaches 15-20 microns. The material fineness is tested by a laser particle size analyzer to ensure that it meets the requirements. The ground wall paint is filtered through a 150-mesh filter to obtain the wall paint.

[0030] Embodiment 4:

[0031] like Figure 1 As shown, a method for preparing an anti-fouling wall paint proposed by the present invention, the steps are described in detail below.

[0032] Preparation of silicone modified acrylic emulsion: 83 parts of deionized water are added to a four-necked flask with a stirring device, a reflux condenser, a thermometer and a dropping funnel by weight. Stirring is started and the speed is set to 180 rpm. 0.1 parts of sodium bicarbonate buffer are added to completely dissolve it. The temperature is slowly raised to 88°C and kept constant. 18 parts of vinyl trimethoxy silane are added to the four-necked flask within 22 minutes to make it preliminarily uniformly dispersed in the reaction system. Methyl acrylate and methyl methacrylate are selected as acrylic monomers in a mass ratio of 1:1. The mixture is added through a dropping funnel at 1. 63 parts of the mixed acrylic acid monomer were added dropwise within 8 hours, and 0.45 parts of the initiator solution prepared by ammonium persulfate were added dropwise at a uniform speed; after the addition was completed, the stirring reaction was continued for 4.5 hours. During the reaction, the volatile substances produced by the reaction were removed in time through a reflux condenser to maintain the stability of the reaction system. After the reaction was completed, the mixture was cooled to room temperature, and unreacted monomers were removed by vacuum distillation at a pressure of -0.08 MPa. The emulsion was filtered through a 180-mesh filter to remove possible insoluble particles, thereby obtaining an organosilicon-modified acrylic acid emulsion; Preparation of modified nano titanium dioxide: using nano titanium dioxide with a particle size between 20 and 50 nanometers for surface modification, using silane coupling agent KH570, adding 2.5% of the mass of nano titanium dioxide, reacting for 1.8 hours under high-speed stirring to obtain modified nano titanium dioxide; First, calcine the diatomite at a high temperature of 950°C for 2.8 hours, then treat it with 8% hydrochloric acid solution for 4.5 hours, then rinse it repeatedly with deionized water until it is neutral, and dry it for later use; The nano-scale hollow glass microspheres were hydrophilized before use, specifically using a composite system of surfactants Span-80 and Tween-80, with a mass ratio of 1:1 and an addition amount of 0.9% of the mass of the hollow glass microspheres, and then dispersed by ultrasound for 50 minutes for use; Weigh the following raw materials in parts by weight: 38 parts of organosilicon-modified acrylic emulsion, 7 parts of modified titanium dioxide, 14 parts of diatomaceous earth, 4 parts of nano-scale hollow glass microspheres, 2.8 parts of film-forming aid, 0.8 parts of polymer dispersant, 0.45 parts of organosilicon defoamer, 0.45 parts of cellulose thickener, 18 parts of pigment, the film-forming aid is alcohol ester-12, the defoamer is BYK028, and the thickener is a hydrophobically modified alkali swelling thickener; Pre-dispersion stage: add deionized water to the high-speed stirring equipment, start stirring at a speed of 300-500 rpm, add dispersant, stir for 14 minutes to completely dissolve it, then add modified nano titanium dioxide, diatomaceous earth, hydrophilic treated nano hollow glass microspheres and pigment in sequence, and continue stirring for 55 minutes; Emulsion mixing stage: reduce the stirring speed to 180 rpm, add the silicone-modified acrylic emulsion, and continue stirring for 28 minutes after the emulsion is added; Additives adding stage: add film-forming additives, defoamers, thickeners in turn, stir for 9 minutes after adding each additive, and then transfer the mixed materials to the sand mill. The grinding medium is zirconium oxide beads, the particle size is controlled between 0.1-1 mm, and the filling amount is 65% of the volume of the grinding equipment. The grinding time is 3.5 hours, and the grinding temperature is controlled at 35°C by circulating cooling water. After multiple cycles of grinding, the material fineness reaches 15-20 microns. The material fineness is tested by a laser particle size analyzer to ensure that it meets the requirements. The ground wall paint is filtered through a 180-mesh filter to obtain the wall paint.

[0033] Embodiment 5:

[0034] like Figure 1 As shown, a method for preparing an anti-fouling wall paint proposed by the present invention, the steps are described in detail below.

[0035] Preparation of silicone-modified acrylic emulsion: 85 parts of deionized water are added to a four-necked flask with a stirring device, a reflux condenser, a thermometer and a dropping funnel by weight, stirring is started, the speed is set to 200 rpm, 0.12 parts of sodium bicarbonate buffer are added to completely dissolve it; the temperature is slowly raised to 90°C and kept constant, 20 parts of vinyltrimethoxysilane are added to the four-necked flask within 25 minutes to make it preliminarily evenly dispersed in the reaction system; methyl acrylate and methyl methacrylate are selected as acrylic monomers and mixed in a mass ratio of 1:1, and the mixture is passed through a dropping funnel. Add 65 parts of the mixed acrylic acid monomer dropwise within 2 hours, and simultaneously add 0.5 parts of the initiator solution prepared by ammonium persulfate dropwise at a uniform speed; continue to stir and react for 5 hours after the addition is completed, and in the reaction process, remove the volatile substances produced by the reaction in time through a reflux condenser to maintain the stability of the reaction system; after the reaction is completed, cool to room temperature, remove the unreacted monomers by a reduced pressure distillation method at a pressure of -0.08MPa, and filter the emulsion with a 200-mesh filter to remove possible insoluble particles to obtain an organosilicon-modified acrylic acid emulsion; Preparation of modified nano titanium dioxide: using nano titanium dioxide with a particle size between 20 and 50 nanometers for surface modification, adding silane coupling agent KH570 at 3% of the mass of nano titanium dioxide, reacting for 2 hours under high-speed stirring to obtain modified nano titanium dioxide; First, calcine the diatomite at a high temperature of 1000°C for 3 hours, then treat it with a 10% hydrochloric acid solution for 5 hours, then rinse it repeatedly with deionized water until it is neutral, and dry it for later use; The nano-scale hollow glass microspheres were hydrophilized before use, specifically using a composite system of surfactants Span-80 and Tween-80, with a mass ratio of 1:1 and an addition amount of 1% of the mass of the hollow glass microspheres, and then dispersed by ultrasound for 60 minutes for use; Weigh the following raw materials in parts by weight: 40 parts of organosilicon-modified acrylic emulsion, 8 parts of modified titanium dioxide, 15 parts of diatomaceous earth, 5 parts of nano-scale hollow glass microspheres, 3 parts of film-forming aid, 1 part of polymer dispersant, 0.5 parts of organosilicon defoamer, 0.5 parts of cellulose thickener, 20 parts of pigment, the film-forming aid is propylene glycol phenyl ether, the defoamer is BYK022, and the thickener is hydroxyethyl cellulose; Pre-dispersion stage: add deionized water to the high-speed stirring equipment, start stirring at a speed of 500 rpm, add dispersant, stir for 15 minutes to completely dissolve it, then add modified nano titanium dioxide, diatomaceous earth, hydrophilic treated nano hollow glass microspheres and pigment in sequence, and continue stirring for 60 minutes; Emulsion mixing stage: reduce the stirring speed to 200 rpm, add the silicone-modified acrylic emulsion, and continue stirring for 30 minutes after the emulsion is added; Additive addition stage: add film-forming additive, defoamer, thickener in turn, stir for 10 minutes after adding each additive, then transfer the mixed material to the sand mill, use zirconium oxide beads as grinding media, the particle size is controlled between 0.1-1 mm, and the filling amount is 70% of the volume of the grinding equipment. The grinding time is 4 hours, and the grinding temperature is controlled at 40°C by circulating cooling water. After multiple cycles of grinding, the material fineness reaches 15-20 microns. The material fineness is tested by a laser particle size analyzer to ensure that it meets the requirements. The ground wall paint is filtered through a 200-mesh filter to obtain the wall paint.

[0036] Comparative Example 1 This comparative example is the anti-fouling exterior wall paint prepared in Example 1 of application number 201610553037.6.

[0037] Experimental verification In order to verify the effect of the present invention, experiments were conducted on the wall paints prepared in Examples 1-5 and Comparative Example 1.

[0038] Experimental methods: Anti-fouling performance test: In accordance with GB / T 9278-2008 "Temperature and Humidity for Conditioning and Testing of Paint Samples", the wall paint sample is evenly applied on the standard test wall substrate to prepare the test sample, which is then cured under constant temperature and humidity conditions for the specified time.

[0039] Use the anti-fouling performance test device to evenly spray the simulated stains on the surface of the test sample. After keeping it for a certain period of time (such as 24 hours), clean it using the prescribed cleaning method (such as the wiping method specified in GB / T 23989-2009 "Determination of Solvent Resistance to Wiping of Coatings").

[0040] The stains remaining on the surface of the sample after cleaning were observed and evaluated using a 5-level scoring method, where 5 means no obvious stains remaining and 1 means serious stains remaining. Five parallel samples were tested for each sample, and the average value was taken as the anti-fouling performance score.

[0041] Air permeability test: A gas permeability tester was used to test the air permeability of the prepared wall paint samples in accordance with GB / T 1038-2000 "Plastic Film and Sheeting Gas Permeability Test Method Pressure Difference Method".

[0042] During the test, the sample is sealed in the test chamber, the pressure and flow of the test gas (such as nitrogen) are controlled, the amount of gas passing through the sample per unit time is measured, and the air permeability of the wall paint is calculated in cm³ / (m²・24h・0.1MPa). Each sample is tested 3 times and the average value is taken.

[0043] Water resistance test: Place the prepared wall paint sample into a water resistance test box and test it according to GB / T 1733-1993 "Determination of water resistance of paint film".

[0044] During the test, 2 / 3 of the sample area was immersed in deionized water, and the water temperature was controlled at (23±2)℃. The sample was taken out after immersion for 1 day, 3 days, 7 days, 14 days, 21 days, and 28 days, and the changes on the sample surface were observed, such as whether there was bubbling, whitening, shedding, etc., and the time when these phenomena occurred was recorded. Three parallel samples were tested for each sample.

[0045] Experimental data: Table 1 Antifouling performance score and air permeability test data

[0046] Table 2 Water resistance test data

[0047] Experimental conclusion: From the anti-fouling performance test data, the anti-fouling performance scores of the anti-fouling wall paints prepared in Examples 1-5 of the present invention are all above 4.5, while the comparative example is only 3.5, indicating that the wall paint of the present invention performs better in resisting stains and can effectively reduce stain residues.

[0048] In the air permeability test, the air permeability of the embodiment of the present invention is significantly higher than that of the comparative example, indicating that the wall paint of the present invention can better achieve water vapor exchange between the wall and the outside world, and is helpful to solve the problem of water vapor accumulation inside the wall caused by the dense paint film.

[0049] The water resistance test results show that the wall paint of the embodiment of the present invention did not show any blistering, whitening, or peeling after 28 days of immersion, while the comparative example began to bubble after 7 days and began to peel after 21 days, which fully proves that the wall paint of the present invention has better water resistance and longer service life.

[0050] In summary, through the comparison of experimental data, it can be clearly seen that the anti-fouling wall paint prepared by the present invention is superior to the comparative example in terms of anti-fouling, air permeability and water resistance, effectively solves the problems mentioned in the background technology, and has significant technical advantages.

[0051] The above specific embodiments are only several optional embodiments of the present invention. Based on the technical solutions of the present invention and the relevant inspirations of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.

Claims

1. A method for preparing an anti-fouling wall paint, characterized in that: The following steps are involved: Step S1, preparation of silicone-modified acrylic emulsion, specifically comprising: 75-85 parts by weight of deionized water are added to a four-necked flask equipped with a stirring device, a reflux condenser, a thermometer and a dropping funnel, stirring is started, the speed is set to 100-200 rpm, and 0.08-0.12 parts of sodium bicarbonate buffer are added to completely dissolve the mixture; Slowly raise the temperature to 80-90°C and maintain a constant temperature, add 10-20 parts of vinyltrimethoxysilane into the four-necked flask within 15-25 minutes to make it preliminarily evenly dispersed in the reaction system; Methyl acrylate and methyl methacrylate are mixed in a mass ratio of 1:1 as acrylic acid monomers, 55-65 parts of the mixed acrylic acid monomers are added dropwise through a dropping funnel within 1-2 hours, and 0.3-0.5 parts of an initiator solution prepared by ammonium persulfate are added dropwise at a uniform speed; After the dropwise addition is completed, the reaction is continued with stirring for 3-5 hours. During the reaction, the volatile substances generated by the reaction are promptly removed through a reflux condenser to maintain the stability of the reaction system. After the reaction is completed, the mixture is cooled to room temperature, and unreacted monomers are removed by vacuum distillation at a pressure of -0.08 MPa. The emulsion is filtered through a 100-200 mesh filter to remove possible insoluble particles, thereby obtaining an organosilicon-modified acrylic emulsion; Step S2, preparation of modified nano titanium dioxide, using nano titanium dioxide with a particle size between 20-50 nanometers for surface modification, using silane coupling agent KH570, adding 1%-3% of the mass of nano titanium dioxide, reacting for 1-2 hours under high-speed stirring to obtain modified nano titanium dioxide; Step S3, weighing the following raw materials in parts by weight: 30-40 parts of organosilicon-modified acrylic emulsion, 5-8 parts of modified titanium dioxide, 10-15 parts of diatomaceous earth, 3-5 parts of nano-scale hollow glass microspheres, 2-3 parts of film-forming aid, 0.5-1 part of polymer dispersant, 0.3-0.5 parts of organosilicon defoamer, 0.2-0.5 parts of cellulose thickener, and 10-20 parts of pigment; Step S4, pre-dispersion stage: add deionized water to a high-speed stirring device, start stirring at a speed of 300-500 rpm, add a dispersant, stir for 10-15 minutes to completely dissolve it, then add modified nano titanium dioxide, diatomaceous earth, hydrophilic treated nano hollow glass microspheres and pigment in sequence, and continue stirring for 30-60 minutes; Step S5, emulsion mixing stage: reducing the stirring speed to 100-200 rpm, adding the organosilicon-modified acrylic emulsion, and continuing stirring for 15-30 minutes after the emulsion is added; Step S6, additive adding stage: add film-forming additive, defoamer and thickener in sequence, stir for 5-10 minutes after adding each additive, then grind and filter to obtain wall paint.

2. The method for preparing an antifouling wall paint according to claim 1, characterized in that: The diatomaceous earth is treated before use, and the specific steps are: first calcining the diatomaceous earth at a high temperature of 800-1000°C for 2-3 hours, then acid-treating it with a 5%-10% hydrochloric acid solution, soaking it for 3-5 hours, then repeatedly rinsing it with deionized water until it is neutral, and drying it for use.

3. The method for preparing an antifouling wall paint according to claim 1, characterized in that: The nanoscale hollow glass microspheres are hydrophilically treated before use, specifically using a composite system of surfactants Span-80 and Tween-80, with a mass ratio of 1:1 and an addition amount of 0.5%-1% of the mass of the hollow glass microspheres, and are ultrasonically dispersed for 30-60 minutes for use.

4. The method for preparing an antifouling wall paint according to claim 1, characterized in that: The film-forming aid is alcohol ester-12 or propylene glycol phenyl ether.

5. The method for preparing an antifouling wall paint according to claim 1, characterized in that: The defoamer is BYK022 or BYK028.

6. The method for preparing an antifouling wall paint according to claim 1, characterized in that: The thickener is hydroxyethyl cellulose or a hydrophobically modified alkali swelling thickener.

7. The method for preparing an antifouling wall paint according to claim 1, characterized in that: Step S3, weighing the following raw materials in parts by weight: 32-38 parts of organosilicon-modified acrylic emulsion, 5-7 parts of modified titanium dioxide, 11-14 parts of diatomaceous earth, 4-5 parts of nano-scale hollow glass microspheres, 2-3 parts of film-forming aid, 0.6-0.8 parts of polymer dispersant, 0.4-0.5 parts of organosilicon defoaming agent, 0.2-0.4 parts of cellulose thickener, and 12-18 parts of pigment.

8. The method for preparing an antifouling wall paint according to claim 1, characterized in that: In the step S3, the following raw materials are weighed in parts by weight: 35 parts of organosilicon-modified acrylic emulsion, 6.5 parts of modified titanium dioxide, 12.5 parts of diatomaceous earth, 4 parts of nano-scale hollow glass microspheres, 2.5 parts of film-forming aid, 0.75 parts of polymer dispersant, 0.4 parts of organosilicon defoamer, 0.35 parts of cellulose thickener, and 15 parts of pigment.

9. The method for preparing an antifouling wall paint according to claim 1, characterized in that: The grinding specifically includes: transferring the mixed material to a sand mill, using zirconium oxide beads as the grinding medium, controlling the particle size between 0.1-1 mm, and filling 50%-70% of the volume of the grinding equipment. The grinding time is 2-4 hours, the grinding temperature is controlled at 20-40°C by circulating cooling water, and the material fineness reaches 15-20 microns after multiple cycles of grinding. The material fineness is tested by a laser particle size analyzer to ensure that it meets the requirements.

10. The method for preparing an antifouling wall paint according to claim 1, characterized in that: The filtering specifically comprises: filtering the ground wall paint through a 100-200 mesh filter to obtain the wall paint.

Citation Information

Patent Citations

  • Synthesis method of organic silicon modified acrylate copolymer

    CN102464784A

  • Reflecting heat-insulation flame-retardant paint and preparation method thereof

    CN102719150A

  • Preparation method of high-performance anti-pollution exterior wall paint

    CN105907217A

  • Self-cleaning reflective thermal insulation coating and preparation method thereof

    CN108467647A

  • Preparation method of novel paint coating

    CN109054510A